The Transcription Factor T-Bet Is Regulated by MicroRNA-155 in Murine Anti-Viral CD8+ T Cells via SHIP-1 - Hope, Jennifer L.; Stairiker, Christopher J.; Spantidea, Panagiota I.; Gracias, Donald T.; Carey, Alison J.; Fike, Adam J.; van Meurs, Marjan; Brouwers-Haspels, Inge; Rijsbergen, Laurine C.; Fraietta, Joseph A.; Mueller, Yvonne M.; Klop, Rosemarieke C.; et al. (Frontiers in Immunology, 2017)
We report here that the expression of the transcription factor T-bet, which is known to be required for effector cytotoxic CD8+ T lymphocytes (CTL) generation and effector memory cell formation, is regulated in CTL by miR-155. Importantly, we show that the proliferative effect of miR-155 on CD8+ T cells is mediated by T-bet. T-bet levels in CTL were controlled in vivo by miR-155 via SHIP-1, a known direct target of miR-155, and SHIP-1 directly downregulated T-bet. Our studies reveal an important and unexpected signaling axis between miR-155, T-bet, and SHIP-1 in in vivo CTL responses and suggest an important signaling module that regulates effector CTL immunity.